Comparison of Robotic Percutaneous Coronary Intervention With Traditional Percutaneous Coronary Intervention: A Propensity Score–Matched Analysis of a Large Cohort. (May 2020) - Patel, Tejas M.; Shah, Sanjay C.; Soni, Yash Y.; Radadiya, Rajni C.; Patel, Gaurav A.; Tiwari, Pradyot O.; Pancholy, Samir B.
Abstract : Background: Robotic percutaneous coronary intervention (R-PCI) has been shown to benefit the operator but has not shown any significant benefit to the patient. We sought to compare a large cohort of R-PCI to traditional percutaneous coronary intervention (PCI) procedures performed at a tertiary care center in the same time frame. Methods: A total of 996 consecutive patients referred for PCI between December 2017 and March 2019 were studied, of which 310 (31.1%) patients were selected to undergo R-PCI and 686 (68.9%) patients underwent traditional PCI. The coprimary study outcome measures were air kerma, dose-area product, fluoroscopy time, volume of contrast, and total procedural time. Caliper propensity-matching technique was used (caliper, 0.05) to match each R-PCI patient to the nearest traditional PCI patient without replacement. Results: Air kerma (mGy; median [interquartile range]; P ; 884 [537–1398] versus 1110 [699–1498]; P =0.002) and dose-area product (cGycm 2 ; 4734 [2695–7746] versus 5746 [3751–7833]; P =0.003) were significantly lower in the R-PCI group. There was no difference in fluoroscopy time (minutes; 5.51 [3.53–8.31] versus 5.48 [3.31–9.37]; P =0.936) and contrast volume (mL; 130 [103–170] versus 140 [100–180]; P =0.905). Total procedural time (minutes) was significantly higher in the R-PCI group (27 [21–40] versus 37 [27–50]; P <0.0005). Conclusions: R-PCI is associated with a significant decrease in radiation exposure to the patient with no increase in fluoroscopy time, as well as contrast utilization, and a minor increase in procedure duration compared with traditional PCI. Abstract : Supplemental Digital Content is available in the text.